Inflorescence structure in Rhynchospora Vahl (Cyperaceae) - Lucero, Leandro Exequiel (2012)
We investigated the inflorescence structure of Rhynchospora following the methodology and terminology of Troll's school, with the objective of providing a characterization of the inflorescence suitable to evaluate the processes responsible for the diversity observed. Homogenization of inflorescence structures may occur fully or partially. In the first case, all branches of the inflorescence are homogeneous, while in the later, distal and proximal parts of the inflorescence bear homogeneous branches, but in the middle portions of the inflorescence non-homogeneous branches exist. Other characters leading to different forms of inflorescences are branching degree, internode elongation along the main axis of the synflorescence, degree of epipodium elongation of distal paraclades, development of bract and prophyll, and development of prophyllar paraclades. We identified three main types of inflorescences: (1) partially homogeneous paniculodia, (2) partially homogeneous capitate heads, and (3) a fully homogeneous capitate head. Within the first type, four subtypes were also recognized. Finally, we discuss how these processes can operate to produce the variation of the inflorescence shape.